PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITASPELANGGAN MELALUI KEPERCAYAAN (Pada Pelanggan Loris Beauty Clinic Malang) - Amaliatus Zahrotul Ula; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This research was conducted to analyze the direct influence and indirect influence of service quality on customer loyalty through customer trust. with the aim of knowing the description of service quality, customer loyalty and trust.The population used in this study is Loris Beauty Clinic Malang customers. Determination of samples using purposive sampling technique. Based on the criteria obtained 89 respondents. The type of research used is explanatory research. Methods of collecting data using questionnaires. Data analysis method uses path analysis. While the data analysis tool used validity test, reliability test, nomination test, with hypothesis testing using the t test and sobel test.The results of this study indicate that service quality variables have a positive and significant effect on trust, service quality variables have a significant positive effect on loyalty, the trust variable has a significant positive effect on loyalty, the trust variable can mediate the effect of service quality on loyalty.Keywords: Service Quality, Customer Loyalty and Customer Trust.